Potensi Hasil Ikutan Ternak Sapi Pedaging Ketika Idul Adha di Sekolah Peternakan Rakyat Ngudi Rejeki, Kediri - Tri Setyani; Mochammad Sriduresta Soenarno (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Beef cattle is of the great ruminants that produce the main products is meat, the beef is used as the fulfillment of food needs, especially animal protein by the community. Most of the Indonesian population is Islam, in Islam one of the great days is Eid al-Adha. Where Eid al-Adha is a moment to sacrifice its wealth for those who can afford it. The usual to be sacrificed are cows, goats, sheep, camels. Beef cattle is one of used by Indonesians to sacrifice. In the process of cattle cutting during the sacrificial season will produce the by-product after slaughtering process. The by-product are head, teeth, bones, cow-hide, blood, offals, legs. The average of the results by-product when Eid al-Adha season are not fully used well by community in Ngadiluwih, Kediri. The results of the by-products was used only the offals to be processed by the community, while the cow-hide was sold and the others were discarded by them. Keywords: beef cattle, eid al-adha, livestock of by-product